Assessing changes in the sprint force-velocity profile following plyometric training in young Football players by maturity status - Fernández-Jávega, G.; Moya-Ramón, M.; Peña-González, I. (Research Quarterly for Exercise and Sport, 2025)
This study assessed changes in the sprint force-velocity (Fv) profile of young football players according to their maturity status following an 8-week plyometric training program. Jump (CMJ) and sprint performance (5-m and 30-m) of 34 players were evaluated, and the sprint Fv profile was calculated. Participants were categorized based on their years from/to peak height velocity (PHV). The training program included three football-specific training sessions and two strength-training sessions with plyometric exercises per week. MANOVA revealed initial differences between maturity groups in body mass, height, 5-m and 30-m sprint times, CMJ, and sprint Fv variables, though the overall profile remained consistent (same slope). Repeated-measures analysis showed a positive effect of the training program (F = 12.18-72.07; p < .001), with improvements in CMJ, 5-m and 30-m sprint times (Cohen`s d = 0.41 to 0.54; p < .050), and sprint mechanical variables (except for a decrease in the ratio of force). Multivariate analysis did not reveal between-group differences in changes post-training (F = 0.05-3.79; p = .060-.826), and standardized effects indicated trivial to small differences in adaptations to the training. This study identified differences in the sprint Fv profile among players of varying maturity status. However, players across different maturity levels improved their sprint Fv profiles similarly, suggesting comparable training responses.